2004
DOI: 10.1002/pola.20406
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic poly(glycidyl methacrylate) microspheres prepared by dispersion polymerization in the presence of electrostatically stabilized ferrofluids

Abstract: Fine magnetite nanoparticles, both electrostatically stabilized and nonstabilized, were synthesized in situ by precipitation of Fe(II) and Fe(III) salts in alkaline medium. Magnetic poly(glycidyl methacrylate) (PGMA) microspheres with core‐shell structure, where Fe3O4 is the magnetic core and PGMA is the shell, were obtained by dispersion polymerization initiated with 2,2′‐azobisisobutyronitrile (AIBN), 4,4′‐azobis(4‐cyanovaleric acid) (ACVA), or ammonium persulfate (APS) in ethanol containing poly(vinylpyrrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…The surfactants often used to stabilize magnetic nanoparticles are based on hexadecyltrimethylammonium bromide or anionic sodium dodecylbenzenesulfonate. As it was found in our previous study that the anionic Fe 3 O 4 was found to be superior to the cationic one in terms of a higher amount of iron oxide incorporated in the product [13], a negative charge was introduced onto the particle surface by TMAH also in this study. Fig.…”
Section: Iron Oxide Colloidsmentioning
confidence: 72%
“…The surfactants often used to stabilize magnetic nanoparticles are based on hexadecyltrimethylammonium bromide or anionic sodium dodecylbenzenesulfonate. As it was found in our previous study that the anionic Fe 3 O 4 was found to be superior to the cationic one in terms of a higher amount of iron oxide incorporated in the product [13], a negative charge was introduced onto the particle surface by TMAH also in this study. Fig.…”
Section: Iron Oxide Colloidsmentioning
confidence: 72%
“…The mPGMA beads were synthesized by dispersion polymerization in a magnetically driven, sealed polymerization reactor equipped with a temperature control system [15,16] as reported elsewhere [17]. Fe 3 O 4 (0.05 g) nanoparticles were dispersed in 68 g of aqueous ethanol solution (96%) by sonication for 30 min at 200 W in an ultrasonic water bath (Sonorex Super 10 P, Bandelin, Germany).…”
Section: Synthesis Of the Mpgma Beadsmentioning
confidence: 99%
“…Mostly, Fe 3 O 4 has been used as the magnetic core and polymers such as polystyrene [14], poly(glycidyl methacrylate) [15], and polyvinyl alcohol [16] have been used as the shells. Recently, micro-or miniemulsion polymerization has been widely used due to its easiness to obtain surface-functionalized microspheres with uniform particle dispersion.…”
Section: Introductionmentioning
confidence: 99%